2004
DOI: 10.1038/sj.ejhg.5201232
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of five candidate genes in Chinese patients with hypospadias

Abstract: Hypospadias is the displacement of the urethral meatus from the tip of the glans to the ventral side of the phallus. During fetal development, SRY, SOX9, WT1, SRD5A2 and AR are important at different stages in the differentiation and development of the male genital system. Mutations in these genes impair masculinization and may be associated with hypospadias. In order to explore these possibilities, we employed polymerase chain reaction and direct sequencing to analyze the coding regions of these five genes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
106
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(118 citation statements)
references
References 20 publications
7
106
0
3
Order By: Relevance
“…Patient 16 carries the hemizygous p.A620V in MID1 (unpublished data), the heterozygous Q6X and G203S mutations in SRD5A2. 4 Family studies found that, in the patient, the hemizygous p.A620V in MID1 is de novo. In addition, family studies also found that his mother, the carrier of the heterozygous p.P42T in HOXB6 and the heterozygous G203S in SRD5A2, and his father, the carrier of the heterozygous Q6X in SRD5A2, were all healthy.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Patient 16 carries the hemizygous p.A620V in MID1 (unpublished data), the heterozygous Q6X and G203S mutations in SRD5A2. 4 Family studies found that, in the patient, the hemizygous p.A620V in MID1 is de novo. In addition, family studies also found that his mother, the carrier of the heterozygous p.P42T in HOXB6 and the heterozygous G203S in SRD5A2, and his father, the carrier of the heterozygous Q6X in SRD5A2, were all healthy.…”
Section: Discussionmentioning
confidence: 90%
“…Some known candidate genes for hypospadias such as SRD5A2, WT1 and AR have already been studied in the 90 patients and some of these patients parents. 4 A total of 190 Chinese normal males with no history of any abnormalities in urogenitory system, limbs and palate, were recruited as a control group. The mean age of the control group was 27 years.…”
Section: Patients and Controlsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous findings could not be generalised to a Chinese population in our study. Large Chinese sample sizes for MAMLD1 in Chinese populations are currently absent (18), and the frequency of MAMLD1 mutations in a larger sample from a Chinese population should be investigated.…”
Section: Discussionmentioning
confidence: 99%